Experiences and expectations of pregnant women using medicinal plants for childbirth preparation in the Kananga Health Zone, Democratic Republic of the Congo - Kapinga, Charlotte Kabamusu; Kabambi, Franck Tshimbila; Tshiama, Ruth Claudine; Mawunu, Monizi; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Ntumba, Joséphine Kankolongo; Omanyondo, Marie-Claire Ohambe; Mukandu, Basua Babintu Leyka (Orapuh Journal, 2025)
Introduction The use of medicinal plants to prepare for childbirth is a widespread traditional practice in many communities. This practice is influenced by cultural beliefs and economic constraints that limit access to modern medical care. These plants are perceived to help shorten labour, relieve contraction pain, and prevent postpartum complications such as haemorrhage. However, scientific data on their actual effects remain limited. Purpose This study aims to explore the lived experiences and expectations of women who used medicinal plants during pregnancy, highlighting perceived benefits and any reported side effects associated with this practice. Methods A qualitative phenomenological study was conducted using an exploratory approach. Data were collected through semi-structured interviews with 20 women who had used medicinal plants during pregnancy, alongside participant observation of 15 of them. A categorical thematic analysis was performed to identify common motivations and perceptions regarding the effectiveness of these traditional practices. Results All participants were married, aged between 23 and 35 years, with a significant proportion having married early. Most (80%) had secondary education, and 55% were housewives. The most commonly used plants included Gynandropsis gynandra, Erythrophleum suaveolens, and Bridelia ferruginea. Deliveries were generally quick (between 5 and 9 hours), with regular contractions, and 95% of cases were eutocic. At one minute, 75% of newborns had an optimal APGAR score. The women reported benefits such as reduced pain, shorter labour, and easier recovery. However, some noted undesirable effects, including a decrease in sexual sensitivity. Conclusion The study highlights the cultural significance and perceived effectiveness of medicinal plants in childbirth preparation. Nonetheless, the occurrence of side effects points to the need for further clinical research to better understand their efficacy and ensure safe use.